Greene, The Presidency Of Gerald R. Ford - Neal, Donn (Teaching History: A Journal of Methods, 1996)
Gerald R. Ford and Jimmy Carter seem fated to be linked together, both in the popular mind and in historical interpretation. Most Americans would probably describe them as decent men who tried their best in difficult times, with modest if any success and few if any lasting accomplishments. In fact, most people might have difficulty differentiating between the two presidents. Oh, the occasional person would mention Ford’s pardon of Richard Nixon, and surely Carter’s role in brokering a framework for peace in the Middle East would not go entirely unnoticed.